The Use of Artificial Intelligence in Dispute Resolution Through Arbitration: The Potential and Challenges - Agus, Agus; Sudirman, Sudirman; Umar, Wahyudi; Rustan, Ahmad (SASI, 2023)
Introduction: The use of artificial intelligence (AI) in dispute resolution through arbitration has become an increasingly relevant topic in the legal world. AI can speed up the process of data collection, data analysis, and provide predictions and recommendations in dispute resolution. However, the use of AI also raises some challenges and risks that need to be overcome.Purposes of the Research: This paper intends to explore the potential of the use of Artificial Intelligence (AI) Technology in dispute resolution through arbitration, as well as the challenges and risks associated with its use. Methods of the Research: The research method used is normative research by analyzing various literature and regulations related to the use of AI in dispute resolution through arbitration. Results of the Research: The results showed that the use of AI in dispute resolution through arbitration can speed up the process and improve the accuracy of data analysis. However, its use also has challenges and risks such as the risk of error and the inability of AI to understand the legal nuances and human factors in the dispute resolution process. To minimize risks and ensure fairness and legal certainty in the dispute resolution process through arbitration, clear regulations and standards are needed in the use of AI. In addition, users and legal practitioners involved in the dispute resolution process through arbitration also need to improve understanding and knowledge of AI technologies.